Night fall: A Novel - Demille, Nelson (New York : Warner Books, 2004)
On a Long Island beach at dusk, Bob Mitchell and Janet Whitney conduct their illicit love affair in front of a video camera, set to record each steamy moment. Suddenly a terrible explosion lights up the sky. Grabbing the camera, the couple flees as approaching police cars speed toward the scene. Five years later, the crash of Flight 800 has been attributed to a mechanical mal-function. But for John Corey and Kate Mayfield, both members of the Elite Anti-terrorist Task Force, the case is not closed. Suspecting a cover-up at the highest levels and disobeying orders, they set out to find the one piece of evidence that will prove the truth about what really happened to Flight 800-the videotape that shows a couple making love on the beach and the last moments of the doomed ailiner.
edited hb 2015-06-16
Keywords: TWA Flight 800 Crash, 1996.; Aircraft accidents -- Investigation -- Fiction; Government investigators -- Fiction; Terrorism -- Fiction; Long Island (N.Y.) -- Fiction; Suspense fiction